UPAYA PREVENTIF CEGAH KEJAHATAN SIBER DAN PENYALAHGUNAAN TRANSAKSI ELEKTRONIK MELALUI SOSIALISASI UU ITE - Aditya, Addin (Jurnal AbdiMas Nusa Mandiri, 2024)
Cyber security is a crucial aspect in today's digital era, especially with the increasing use of electronic transactions in various sectors of society. Through a community service approach, this programme implements a series of counseling activities, and a cybersecurity awareness campaign in Sukun Sub-district. This activity aims to increase cyber security awareness and electronic transactions in Sukun Sub-district, Malang City. The methods used include seminars and distribution of educational materials. Evaluation was conducted to measure the effectiveness of the programme in improving the knowledge and behavior of the community regarding cyber security and electronic transactions. The results of the activity evaluation questionnaire showed a significant increase in community understanding and awareness of cybersecurity threats and steps that can be taken to protect themselves when conducting electronic transactions. In conclusion, the community service approach is an effective strategy in increasing cybersecurity awareness and electronic transactions in Sukun Sub-district, Malang City. It is hoped that this activity can make a positive contribution in creating a safer and more trusted digital environment for the community.